(untitled) (IJM: Journal of Multidisiplinary, 2025)
This study aims to determine the extent of the influence of Live Streaming, Price Perception, and Online Customer Reviews on the purchasing decisions of Wardah makeup products in East Bekasi through the TikTok Shop platform. The research uses a descriptive quantitative approach, which aims to describe the relationships between the variables being studied. Data collection was carried out by distributing questionnaires to 100 respondents who met certain criteria, using a Non-Probability Sampling method with purposive sampling technique. The data analysis technique used was multiple linear regression analysis, processed using SPSS version 25 software. Based on the analysis results, this study found that the variables of Live Streaming, Price Perception, and Online Customer Reviews have a positive and significant effect on purchasing decisions. Although the Live Streaming variable shows a positive influence, its effect is not significant on a partial basis, while Price Perception and Online Customer Reviews were found to have a positive and significant influence on the purchasing decisions of Wardah makeup products on TikTok Shop.